Mayflies (Ephemeroptera) and Their Contributions to Ecosystem Services - Luke M. Jacobus; Craig R. Macadam; Michel Sartori (2019)
This work is intended as a general and concise overview of Ephemeroptera biology, diversity, and services provided to humans and other parts of our global array of freshwater and terrestrial ecosystems. The Ephemeroptera, or mayflies, are a small but diverse order of amphinotic insects associated with liquid freshwater worldwide. They are nearly cosmopolitan, except for Antarctica and some very remote islands. The existence of the subimago stage is unique among extant insects. Though the winged stages do not have functional mouthparts or digestive systems, the larval, or nymphal, stages have a variety of feeding approaches—including, but not limited to, collector-gatherers, filterers, scrapers, and active predators—with each supported by a diversity of morphological and behavioral adaptations. Mayflies provide direct and indirect services to humans and other parts of both freshwater and terrestrial ecosystems. In terms of cultural services, they have provided inspiration to musicians, poets, and other writers, as well as being the namesakes of various water- and aircraft. They are commemorated by festivals worldwide. Mayflies are especially important to fishing. Mayflies contribute to the provisioning services of ecosystems in that they are utilized as food by human cultures worldwide (having one of the highest protein contents of any edible insect), as laboratory organisms, and as a potential source of antitumor molecules. They provide regulatory services through their cleaning of freshwater. They provide many essential supporting services for ecosystems such as bioturbation, bioirrigation, decomposition, nutrition for many kinds of non-human animals, nutrient cycling and spiraling in freshwaters, nutrient cycling between aquatic and terrestrial systems, habitat for other organisms, and serving as indicators of ecosystem health. About 20% of mayfly species worldwide might have a threatened conservation status due to influences from pollution, invasive alien species, habitat loss and degradation, and climate change. Even mitigation of negative influences has benefits and tradeoffs, as, in several cases, sustainable energy production negatively impacts mayflies.